2010
DOI: 10.1021/la100980x
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanoparticle Photophysics and Singlet Oxygen Generation

Abstract: The effect of molecular oxygen and water on the blue photoluminescence of silicon nanoparticles synthesized by anodic oxidation of silicon wafers and surface functionalized with 2-methyl 2-propenoic acid methyl ester is investigated. The particles of 3 +/- 1 nm diameter and a surface composition of Si(3)O(6)(C(5)O(2)H(8)) exhibit room-temperature luminescence in the wavelength range 300-600 nm upon excitation with 300-400 nm light. The luminescence shows vibronic resolution and high quantum yields in toluene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 35 publications
3
50
0
1
Order By: Relevance
“…Initially, our proposed phenomenological model, featuring an environmentally derived adsorbed layer, agrees with previous reports that emphasize the impact of water adsorption on electric charge transport at the Nanoscale [30], and the feasibility of physisorbed O 2 to quench Si nanoparticle luminescence at room temperature [30]. Furthermore, humidity has reportedly produced deleterious effects on organic thin film transistors [32].…”
Section: B Diode Model: Effects Of Electron Beam Irradiation and Sursupporting
confidence: 87%
See 2 more Smart Citations
“…Initially, our proposed phenomenological model, featuring an environmentally derived adsorbed layer, agrees with previous reports that emphasize the impact of water adsorption on electric charge transport at the Nanoscale [30], and the feasibility of physisorbed O 2 to quench Si nanoparticle luminescence at room temperature [30]. Furthermore, humidity has reportedly produced deleterious effects on organic thin film transistors [32].…”
Section: B Diode Model: Effects Of Electron Beam Irradiation and Sursupporting
confidence: 87%
“…Indeed, Dierre et al [1] found that NBE-CL signal could either increase or decrease upon t-evolved e-beam irradiation as a function of surface termination. In fact, the suitability adsorbed surface species (molecular oxygen and water) to strongly modify time-dependent luminescence at room temperature has been confirmed recently [30].…”
Section: Research Articlementioning
confidence: 88%
See 1 more Smart Citation
“…More recent trend in this area has been testing of metal nanoparticles such as gold and platinum nanoparticles for DNA degradation studies [14,15]. Use of metal nanoparticles can be in particular advantageous in generating singlet oxygen [16,17]. A recent report by Geddes and coworkers demonstrated that the presence of metal nanoparticles can enhance singlet oxygen generation [18].…”
Section: Resultsmentioning
confidence: 99%
“…A more current development in this area has been testing of metal nanoparticles such as gold and platinum nanoparticles for DNA degradation studies (Shen et al 2009; López et al 2010). Use of metal nanoparticles can be in particular advantageous in generating singlet oxygen [42 and 43] (Lipovsky et al 2009; Portolés et al 2010)…”
Section: Resultsmentioning
confidence: 99%